Hybrid Learning in Arabic Language Instruction: Combining Online and Face-to-Face Learning for Optimal Results - Basyid Jabbar, Abdul; Fadli, Adi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Hybrid learning has emerged as a strategic response to the evolving needs of language education, especially in an era that demands flexibility and technological integration. This study explores the implementation of hybrid learning in Arabic language instruction by combining online and face-to-face learning approaches to achieve optimal outcomes. The main objective is to examine how hybrid learning enhances students’ engagement, linguistic competence, and learning autonomy. Using a qualitative method, the study collects data through classroom observations, in-depth interviews with instructors and students, and document analysis. The results show that hybrid learning offers a balanced approach—leveraging the flexibility of digital platforms while maintaining the interactive and communicative benefits of in-person instruction. This combination effectively increases student motivation and comprehension. Despite challenges such as unequal access to technology and varying levels of digital literacy, the research confirms that with adequate support and planning, hybrid learning significantly improves the quality of Arabic language instruction. Therefore, hybrid learning is concluded to be a viable and adaptive pedagogical model for language education.